Sn-Doped Zinc Oxide as an Electron Transporting Layer for Enhanced Performance in PbS Quantum Dot Solar Cells - Park, Minji; Lim, Chanwoo; Lee, Hyejin; Kang, Byungsoo; Hwang, Hyun Wook; Kim, Seok Ki; Lee, Phillip; Kim, Woong; Yu, Hyeonggeun; Kim, Taehee (ACS Applied Materials and Interfaces, 2024)
Colloidal PbS quantum dot solar cells (QDSCs) have been primarily demonstrated in n-i-p structures by incorporating a solution-processed ZnO electron transporting layer (ETL). Nevertheless, the inherent energy barrier for the electron extraction at the ZnO/PbS junction along with the defective nature significantly diminishes the performance of the PbS QDSCs. In this study, by employing Sn-doped ZnO (ZTO) ETL, we have tuned the conduction band offset at the junction from spike-type to cliff-type so that the electron extraction barrier can be eliminated and the overall photovoltaic parameters can be enhanced (open-circuit voltage of 0.7 V, fill factor over 70%, and efficiency of 11.3%) as compared with the counterpart with the undoped ZnO ETL. The X-ray photoelectron spectroscopy (XPS) analysis revealed a mitigation of oxygen vacancies in the ZTO ETL of our PbS QDSCs. Our work signifies the importance of Sn doping into the conventional ZnO ETL for the superior electron extraction in PbS QDSCs.
Keywords: Doped zinc oxides; Electron extraction; Electron transporting layer; P-structures; PbS quantum dots; Performance; Quantum dot solar cells; Sn-doped; Sn-doped ZnO; Solution-processed; electron transporting layer; oxygen vacancy; PbS quantum dots; Sn-doped ZnO; solar cells; ZnO